KONTRIBUSI NU SEBAGAI ORGANISASI CIVIL SOCIETY DALAM DEMOKRATISASI - Suryani Suryani (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2015)
This paper illustrates how the political dynamics of Nahdlatul Ulama (NU) as a part of civil society in Indonesia in the national political constellation. NU is a concrete example of the people power in the form of civil society whose existence should be noted. As the largest Muslim community in Indonesia, NU was recorded as the entity who contacted and reinforced the concept of civil society in Indonesia earlier than other Muslim modernist communities. NU activists and intellectuals play an earlier role in developing the discourse of civil society since the independence to now compared to Muhammadiyah, HMI alumni, or other Muslim leaders alumni from Masyumi.